Representações de usuários do programa academia da saúde sobre promoção da saúde e prevenção de doenças - Rosana Franciele Botelho Ruas (2016)
The high morbidity and mortality due to chronic non-communicable diseases (NCD), appears as a complex situation and multicausal, in Brazil and in the world, often addressed in research that relate to objectives and measurable factors, and underlying public policies for its prevention and control. The Health Academy program was instituted by the federal Government in 2011 as a health promotion strategy that includes physical activity and health education in specific structures in the Brazilian municipalities. It is expected that participation in the program will result in improvement of the indicators related to NCD, which requires research to consider aspects of subjectivity concerning the accession and changes in behaviour, synthesized in social representations about health and disease. Wonders if there are reconstructions of postures on health and care after insertion into the program. The objective of this study was to understand representations about health and disease of users of the academies of health of Belo Horizonte, Minas Gerais. This is qualitative research, grounded in the theory of social representations, in the perspective of Alain Giami, performed with interviews with 32 users, 11 men and 21 women. The data were interpreted based on the structural analysis of narration and unfolded two categories: health and disease: the relationship between the social norm and the possibilities of the subject; Care in ways of living: the influence of gender and age. The representations are anchored in the experiences of respondents, their life stories and social interactions. Representations of health that emphasize the biological reductionist model and focusing on prescriptive rules and conduct, predominate, but representations were found relating to health law and access to basic living conditions, the postures of prevention and care, to the joy of living and leisure, even if these are still blurred compared to first. The findings point to diversity of expectations and conduct vis-à-vis the health and disease determined by age, the female role in the universe of the care is emphasized, but women care for you late due to the demands of social organization, within the family and in the world of work. This last is the main justification for the lack of representation of men with health care. The results show that the scenario studied, although persistent, hegemonic representations is building space and possibilities of ruptures, indicating that the professionals of the academies must commit more and more with the expansion and deepening of the understanding of broader conceptions about health, illness and care, considering the importance of psychosocial aspects in the investment in healthy lifestyles. The stock offering should prioritize the autonomy, integrity, equity, founded in the role of the users about their choices.